MODEL PENGEMBANGAN LITERASI INFORMASI DI PERPUSTAKAAN SEKOLAH - Ilham Mashuri (Pustakaloka, 2014)
Abstract: Information literacy as continuing agenda has given school library to develop its facilites. This article  tries to describe how  school libraries develop IL models. With IL, librarians will study more how to use informations resources increasing fast. For user’s, IL will give skills to study for long life, he will be able to understand the need of information, how to fnd, manage, dan use for daily life.Key word: Information Literacy Models, Information Literacy, School library.